Potentially inappropriate medications use and its associated factors among geriatric patients: a cross-sectional study based on 2019 Beers Criteria - Heba Khader; Luai Z. Hasoun; Ahmad Alsayed; Mahmoud Abu-Samak (Pensoft Publishers, 2021)
The aims of this study were to estimate the prevalence of potentially inappropriate medications (PIMs) in a community-dwelling Jordanian population of geriatrics according to the 2019 American Geriatrics Society Beers Criteria, to identify the most used PIMs and factors independently associated with PIMs use. This was an observational, descriptive, cross-sectional study. The sample population included 386 participants. Data were collected by face-to-face interviews. A total of 2894 medications were evaluated. The prevalence of patients using at least one PIM was 49.2%. The most used PIMs were proton pump inhibitors (24.6%) and long-acting sulfonylurea (20.5%). Participants who had diabetes mellitus, peptic ulcer, or irritable bowel syndrome had significantly higher numbers of PIMs. The use of PIMs was high in Jordanian geriatric patients. The results of this study might help healthcare providers to detect high-risk patients and reconsider the necessity of using PIMs to decrease the risk of adverse drug events.